(untitled) (Colombia Medica, 2018)
Introduction: Deletion 22q11.2 occurs in 1:4,000-1:6,000 live births while 10p13p14 deletion is found in 1:200,000 newborns. Both deletions have similar clinical features such as congenital heart disease and immunological anomalies. Objective: We looked for a 22q11.2 deletion in Mexican patients with craniofacial dysmorphisms suggestive of DiGeorge or velocardiofacial syndromes and at least one major phenotypic feature (cardiac anomaly, immune deficiency, palatal defects or development delay). Methods: A prospective study of 39 patients recruited in 2012-2015 at the Instituto Mexicano del Seguro Social at Guadalajara, Mexico. The patients with velocardiofacial syndrome-like features or a confirmed tetralogy of Fallot (TOF) or complex cardiopathy were studied by G-banding and fluorescence in situ hybridization (FISH) with a dual TUPLE1(HIRA)/ARSA or TUPLE1(22q11)/22q13(SHANK3) probe, six patients without the 22q11.2 deletion (arbitrarily selected) were tested with the dual DiGeorge II (10p14)/D10Z1 probe. Results: Twenty-two patients (7 males and 15 females) had the 22q11.2 deletion and 17/39 did not have it; no patient had a 10p loss. Among the 22 deleted patients, 19 had congenital heart disease (mostly TOF). Twelve patients without deletion had heart defects such as TOF (4/12), isolate ventricular septal defect (2/12) or other disorders (6/12). Conclusion: In our small sample about 56% of the patients, regardless of the clinical diagnosis, had the expected 22q11.2 deletion. We remark the importance of early cytogenetic diagnosis in order to achieve a proper integral management of the patients and their families.